Coating and Surface Treatments on Orthodontic Metallic Materials (2023)
Metallic biomaterials have been extensively used in orthodontics throughout history. Gold, stainless steel, cobalt-chromium alloys, titanium and its alloys, among other metallic biomaterials, have been part of the orthodontic armamentarium since the twentieth century. Metals and alloys possess outstanding properties and offer numerous possibilities for the fabrication of orthodontic devices such as brackets, wires, bands, ligatures, among others. However, these materials have drawbacks that can present problems for the orthodontist. Poor friction control, allergic reactions, and metal ionic release are some of the most common disadvantages found when using metallic alloys for manufacturing orthodontic appliances. In order to overcome such weaknesses, research has been conducted aiming at different approaches, such as coatings and surface treatments, which have been developed to render these materials more suitable for orthodontic applications. The purpose of this paper is to provide an overview of the coating and surface treatment methods performed on metallic biomaterials used in orthodontics. © 2013 by the authors.